Prototype Detection System Of Papaya Murability Using Fuzzy Logic Method Based On Color Sensor - Fachrul Rahmadany; Nur Afifah Zen; Danny Kurnianto (Universitas Medan Area, 2023)
Product selection based on the ripeness quality of papaya fruit is one of the stages in the processing of plantation products. At this time, the process of sorting papaya fruit is still using manual methods, especially in estimating the level of ripeness. Papaya is considered a climacteric fruit where respiration occurs and its ethylene production suddenly increases and then rapidly falls off. Fruit with a low respiration rate has a longer shelf life than fruit with a high respiration rate. To overcome this problem, this research created a prototype of a papaya fruit ripeness detection system using a color sensor-based fuzzy logic method. This fruit maturity detector can provide information related to fruit ripeness (unripe, half ripe, and ripe) which is determined from the color of the papaya fruit which is then processed using the Mamdani fuzzy logic method. The results of the prototype design can measure fruit with an accuracy rate of 93.33% of the 30 data tested by using tools that are in a cool place, with low intensity of incoming sunlight. Keywords: Papaya fruit ripeness, TCS3200 Sensor, Mamdani Fuzzy Logic.